Template Preparation Affects 16S rRNA High-Throughput Sequencing Analysis of Phyllosphere Microbial Communities - Tian, Xiaoyan; Shi, Yu; Geng, Lili; Chu, Haiyan; Zhang, Jie; Song, Fuping; Duan, Jiangyan; Shu, Changlong (Frontiers in Plant Science, 2017)
Phyllosphere microbial communities are highly diverse and have important ecological implications; in that context, bacterial identification based on 16S rRNA genes is an important research issue. In studies of phyllosphere microbial communities, microporous filtration and centrifugation are used to collect microorganism samples, but it is unclear which one has a better collection efficiency. In this study, we compared these two microorganism collection methods and investigated the effects of the DNA extraction process on the estimation of microbial community composition and organization. The following four treatments were examined: (A) filtration, resuspension, and direct PCR; (B) filtration, DNA isolation, and PCR; (C) centrifugation, resuspension, and direct PCR; (D) centrifugation, DNA isolation, and PCR. Our results showed that the percentage of chloroplast sequence contaminants was affected by the DNA extraction process. The bacterial compositions clearly differed between treatments A and C, suggesting that the collection method has an influence on the determination of community structure. Compared with treatments B and D, treatments A and C resulted in higher Shannon index values, indicating that the DNA extraction process might reduce the observed phyllosphere microbial alpha diversity. However, with respect to community structure, treatments B and D yielded very similar results, suggesting that the DNA extraction process erases the effect of the collection method. Our findings provide key information to ensure accurate estimates of diversity and community composition in studies of phyllosphere microorganisms.